Written exams:concrete solution to solve image-text relation for visual communication design’students(art students)? - Iwan Zahar; Abdullah Sani Kamaluddin (2011)
Post modern visual culture and semiotic places on emphasis on image as text; consequently, learning now includes the study of both text and image that are made up of many forms of mixed media, and does not separate text from images. Visual Communication Design’s Students have seldom taken written exams, reading text, and writing assignments. Most design’s subject matter emphasize in studio productions. Thus the lecturers have seldom given exams or assignments which relate between text and images. One of design’s subject matter is photography. Most photographic lecturers had never given written exams; instead they gave photo assignments for final project. Most of the lecturers gave either written exams or studio productions, but they have seldom or never integrate the text and images. The survey research conducted on 100 communication design students in third and fifth semester, and three photographic lecturers, in Tarumanagara University. The photographic lecturers prepared learning materials, student’s presentation, and exams with combine text and images. Problem based learning was used to make students more focused on the themes and assignments. Moreover, the lecturers can fasilitates student, supervise student, and provide feed back. Barrett’s photo criticism was used to help students relate text and image of photographs. Some guided question was modified from Barrett’s photo criticism model. The guided questions and images selections became important steps during delivery materials, and listed in lecturer’s presentation and student’s assignments. The guided questions and a good selection of images helped the discussion, and brought students to complex thinking.